Immediate effects of maximal strength training on static balance - Ujakovic, F.; Vucic, D.; Cavar, I.; Miskulin, M.; Mudronja, L. (Acta Kinesiologica, 2014)
The aim of this study was to determine effect maximal strength training on static balance. Eleven Croatian championship rugby players (mean±SD: age, height and weight 22.5 ± 2.7 years, 182.5 ± 6.2 cm, and 92.9 ± 9.5 kg, respectively) volunteered in this study. Players were tested for Transversal both feet standing on balance board with open eyes, Parallel one leg stand on board with open eyes, Perpendicular one leg standing on board with open eyes. Results of this study generally showed that there were no statistical significant differences in results of static balance before and after Maximal Strength Training (MST) (p = 0.32). But, we found that there was statistical significant difference on Transversal both feet standing on balance board (p=0.03). Other two tests showed increasing results on their dominant leg in contrast to the results of non-dominant leg but not statistically significant (p > 0.05). In majority of sports most of the training time is spend on strength and power development, coaches should know that with developing strength and power they affect other abilities in this case balance. This is important practical information for sport coaches because of a lack of time, especially in in-season period.